Assessment Of Knowledge and Awareness Regarding Thyroid Disorders Among Women of a Cosmopolitan City of Central India - Shailesh Rai; Suraj Sirohi; AK Khatri; Sanjay Dixit4 Sanjay Dixit; Satish Saroshe (Medsci Publications, 2016)
Background: Even in 21st century, very few people really know much about the small thyroid gland located at the back of the neck and its vitally important function. Any dysfunction of the thyroid has profound impact on health and well-being. Methods: This cross-sectional study was conducted in September 2014 in 4 different areas of Indore city of MP. 250 females of age group 18-50yrs residing in Indore, belonging to different residential areas. Results: In the study 29.2% females do not have heard the word "THYROID", 48.8 % females had excessive sensitivity to heat or cold, 25.2 % females had constipation/diarrhoea from long time, 61.2% females had joint or muscle pain/weakness, 69.6 % females had anxiety/depression /mood swing, 39.6 % females had menstrual irregularity, 82.4 % females had problem of hair loss/skin changes, 18.67% females have trouble in getting pregnant/repeated miscarriages/stillbirth Only 49.20% females knew about hyperthyroidism and hypothyroidism, 25.2% females have undergone the thyroid screening test, 55.2% females thought that thyroid disorders could be cured by using alternative medicine. Conclusion: In general, the females have inadequate knowledge of thyroid gland, & associated disorders and they had myths and misconception regarding thyroid disorders.